2013
DOI: 10.1177/0300060513476424
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ramadan fasting on serum immunoglobulin G and M, and salivary immunoglobulin A concentrations

Abstract: Objective: To investigate the effects of Ramadan fasting on serum concentrations of immunoglobulin (Ig)G and IgM, and salivary IgA concentrations. Methods: Blood and saliva samples were collected one week before and during the last week of Ramadan from healthy male volunteers. Albumin, total lymphocyte count, electrolytes, and IgG and IgM concentrations were determined in serum; salivary IgA concentrations were measured. Anthropometric measurements were also recorded. Results: Samples were collected from 35 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 35 publications
1
36
0
1
Order By: Relevance
“…Serum IgA, IgG and IgM levels in healthy Iraqi subjects and in patients with type 2 diabetes mellitus were reported to be slightly decreased towards the end of Ramadan [Al-Jewari et al 2007]. Another study on healthy adult Turkish males found decreased concentrations of serum IgG and salivary IgA during Ramadan compared with pre-fast levels, but the IgG concentration remained within the normal range [Develioglu et al 2013]. However, a study on Tunisian judo athletes maintaining training during Ramadan found increased IgA, which remained high 3 weeks later, with no change in leukocyte count [Chaouachi et al 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Serum IgA, IgG and IgM levels in healthy Iraqi subjects and in patients with type 2 diabetes mellitus were reported to be slightly decreased towards the end of Ramadan [Al-Jewari et al 2007]. Another study on healthy adult Turkish males found decreased concentrations of serum IgG and salivary IgA during Ramadan compared with pre-fast levels, but the IgG concentration remained within the normal range [Develioglu et al 2013]. However, a study on Tunisian judo athletes maintaining training during Ramadan found increased IgA, which remained high 3 weeks later, with no change in leukocyte count [Chaouachi et al 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Epinephrine and norepinephrine concentrations were assayed by high-pressure liquid chromatography with electrochemical (amperometric) detection ( 16 ). Nutrional risk index is calculated using the following equation: NRI = 1.519 × serum albumin (g/dL) + 41.7 (present/usual body weight (kg)) ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have found varied effects of Ramadan fasting ( 4 - 16 ). The duration of Ramadan fasting varies among areas of different latitudes.…”
Section: Introductionmentioning
confidence: 99%